Evaluación al sistema actual de contabilización y su incidencia en el manejo de los recursos económicos de la asociación de producción, procesamiento y elaboración de productos de Guadua "Aproguadua" del Cantón El Empalme año 2011 - Mendoza Macías, Flor María (2012)
The accounting system is a structure through which the company collects information as a result of their daily operations, using resources such reports to be presented to management to enable it to make sound financial decisions. The activities carried out in the accounting of the Association of Production, Processing and Products Guadua "APROGUADUA" are developed manually, carried in books, records that support sequential voucher transactions. The association does not have an accounting software, which significantly influence the commission of inadvertent errors that affect the financial management and decision making of the company, which is why I chose this theme: "Assessing the current system of accounting and its impact in managing the financial resources of the Association of Production, Processing and Products Guadua "APROGUADUA" the Canton Junction - 2011." The project used several methods to suggest a proposal based on the results of the investigation, which proposes an accounting system, as a management tool that seamlessly connects to all areas within a single structure, integrating information and optimizing time working to deliver reports that help decision making, control accounting, tax and financial resources of the association.